Effects of aluminum and copper on the graphite morphology, microstructure, and compressive properties of ductile iron - Sazegaran H.; Teimoori F.; Rastegarian H.; Naserian-Nik A.M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The effect of aluminum (0, 2, 4, and 6 wt. %) and copper (0, 2, 4, and 6 wt. %) on graphite morphology, microstructure and compressive behavior of ductile iron specimens manufactured by sand casting technique were investigated. The graphite morphology and microstructure were evaluated using optical microscopy (OM) and scanning electron microscopy (SEM) equipped image processing software. To study the mechanical properties, the compression test was conducted on the ductile iron specimens. The results indicated that the surface fraction and nodule count of graphite decreased when the amount of aluminum increased from 0 to 2 wt. % and after that from 2 to 6 wt. %. In addition, the nodularity of graphite increased with the increment of the aluminum amounts. By adding the amount of copper, the surface fraction and nodule count of graphite increased and nodularity of graphite decreased. The addition of aluminum and copper decreased the surface fraction of ferrite and increased the surface fraction of pearlite in the microstructure. By increasing the amounts of aluminum and copper, compressive stress vs. strain curves were shifted upwards, and modulus of elasticity, yield strength, maximum compressive stress, and fracture strain improved. In comparison with copper, aluminum had a greater influence on the mechanical properties of ductile iron.